Software effective risk management: An evaluation of risk management process models and standards - Jaafar, J. (Springer Verlag, 2015)
Different software risk management process models, professional standards and specific techniques have been presented in literature by researchers and practitioners in the software industry to make the development of software projects more likely to succeed. In this study different software risk management process models and Professional standards have been evaluated against the most effective risk management techniques and processes proposed by the different researchers in the last 13 years to highlight the strengths and weaknesses of different risk management process models. The results show that, there is no model which can be called the de facto effective risk management process model. Â© Springer-Verlag Berlin Heidelberg 2015.